Citizenship and the origins of women's history in the United States - Murphy, Teresa Anne (Democracy, citizenship, and constitutionalism., 2013)
This book challenges twenty-first-century assumptions of nineteenth-century women's history by tracing the ways women's history was politicized, particularly in light of the growing activism of women and the first womens' rights movement.